Motivasi Wisatawan Wanita dan Persepsi Masyarakat Lokal terhadap Klub Gay di Seminyak, Bali - Pratama, Dio; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 7 No 1 (2019): VOL 7, NO 1 (2019): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2019)
This research was conducted to find out the motivation of female tourist to visit Gay club, the perception of the tourist and local community towards the Gay Club. The methods used in this research id descriptive qualitative. The technique of determination of informants used is purposive sampling technique. Data sources used are primary and secondary data sources. Primary data in this research is sourced from direct observation to the research location by means of observation and interviews. While secondary data in this research are the data obtained from the documentation or studies library to complement the primary data. The result of the research shows that most tourist say curious to see Gay club as a motivation for a visit; most tourist plead happy after seeing the atrractions there; most neutral against Gay tourist; most local community already know about Gay club; most local community are not disturbed; most local people are not benefitting from the presence of the Gay club. Keywords : Tourist Motivation, Community Local Perception, Gay Club